The Parametric Form of Z‐Number and Its Application in Z‐Number Initial Value Problem - Pirmuhammadi, S.; Allahviranloo, T.; Keshavarz, M. (International journal of intelligent systems, 2017)
In this paper, the parametric form of Z‐numbers is introduced and it is followed by defining arithmetic operations on them. To suggest Z‐number initial value problem (ZIVP), definition of derivative of Z‐process is necessary. For this purpose, the generalized Hukuhara differentiation and generalized differentiation are defined in details. To solve the mentioned ZIVP, the characterization theorem is proved. Finally, for more illustrations of the subject, some examples are solved and expounded.